The Social Democrats’ Struggle for Power - Larsen, Martin Vinæs; Faarvang, Winnie; Therkelsen, Camilla (Politica, 2020)
The past 30 years have been an electoral fiasco for the Social Democrats in Denmark. In spite of this, they have been able to reclaim power from right-wing parties three times and have controlled the government in almost half the period. This might seem like a paradox. Yet, we argue that the Social Democrats have repeatedly made decisions that were unpopular among their current supports but increased their likelihood of becoming/remaining the governing party. In this way, the Social Democrats have been able to hold on to power, not in spite of but in part because of their electoral losses. We substantiate our argument by re-examining existing analyses of the Social Democrats and re-analyzing data from the Danish National Election Study as well as from public opinion polls.